Complementaty and alternative medicine precautions and potential risk and drug interactions in oral and maxillofacial surgery, periodontics and surgical dentistry - Nicholoff, T. J., Jr.
Health and wellness have become important positive lifestyle goals among the general populace in recent years, encompassing not only the promotion of health and well being, but the prevention and management of illnesses as well. A large part of health & wellness is "self care" oriented and may make use of homeopathic, botanical, nutriceutical products and herbal medicines,which may fall within the realm of Complementary and Alternative Medicine or CAM. Statistical studies demonstrate that a large part of the world's population use some form of CAM. Complementary & Alternative Medicine (CAM) runs the gamut from Herbal Medicine, Nutrition, Vitamins & Dietary Supplements, Mind-Body Medicine, to Alternative Healthcare Practices such as Traditional Chinese Medicine (TVM), Chiropractic, Ayurvedic Medicine and Homeopathy. Once considered "on the fringe" and "quackery", in recent years, some aspects of CAM have gained a degree of respectability and have been integrated into mainstream or conventional medicine and CAM can now be found on the curriculums of some of the most prestigious medical schools in the United States and Europe. (Perlman A; Wetzel MS, et al)
In Germany and France, Herbal Medicine is a significant part of the GP Physician's armamentarium. One study in fact showed that herbal medicines accounted for primary treatment options for up to 40 % of German and French physicians. (Lutz C, et. al; Watkins RW) In the Philippines, like most of Asia, medicinal plants make up a significant part of folk medicine, more commonly practiced in the rural areas; and interest in traditional Philippine herbal remedies has likewise increased.
Currently, the U.S. National Institute of Health (NIH) maintains a National Center for Complementary and Alternative Medicine (NCCM), and has begun evidence-based analysis and double blind studies on may CAM modalities, some of which are now part of "evidence-based medicine". As CAM has grown in popularity and use, certain discoveries ahve shown that not all herbal, botanical or natural products are risk free, and some may have drub-herb interaction potential, anesthetic risks, and surgery related bleeding complications. This short overview examines some of the precautions and potential interactions/complications that could possibly be encountered in the practice of surgical dentistry, oral & maxillofacial surgery, and periodontics.
Keywords: Complementary medicine - Dentistry; Mouth - Diseases - Alternative treatment